Using virtual reality to explain the magical reality of tarot - Argüello Ruíz Oscar Jesús; Uriel-Haile Hernandez-Belmonte (ХНУРЕ, 2022)
The aim of this project is to produce a Virtual Reality experience focused in the Tarot cards and the description of the hero's journey.
Keywords: virtual reality; tarot